Competing ideas: Canada's competition reform conversation - Vass Bednar; Keldon Bester (Centre for International Governance Innovation (CIGI), 2024)
The Government of Canada's recent review of and updates to the Competition Act have sparked a closer examination of how competition is protected and promoted in Canada. Competition affects all Canadians, especially in the face of rising costs of living and a shrinking number of competitors in key markets. Yet the laws that govern competition are not easily understood by average consumers, leaving them out of the public policy conversation. This paper looks at why better competition law is needed and examines previous reform efforts.
Keywords: 330